Discourse on ‘Falsity’ in Heritage Revitalization: The Beautification of Kali Besar Jakarta and Its Impacts on Historic Urban Landscape (HUL) - Euis Puspita Dewi; Kemas Ridwan Kurniawan (Department of Architecture Universitas Muhammadiyah Jakarta, 2019)
This paper aims to raise the issue of